Glad i dyr? En diskusjon av dyriske følelser og følende dyr - Thorsen, Liv Emma (Tidsskrift for kulturforskning, 2003)
The intention of the article is to consider how feelings for animals are manifested socially and culturally. Whereas several surveys have been carried out on how feelings for animals have come to be expressed in the upper urban social class, the farmer’s relationship to domestic animals in the period from approximately 1860 to 1950 has often been formulated through sources generated by outside observers. First by analysing sources generated by persons from the farming community itself, such as responses to questionnaires, diaries, memoirs and the like, is it possible to establish a historical perspective of the mentality of the agricultural society’s relationship to animals The article analyses responses to a questionnaire from Swedish Småland regarding the care of domestic animals. Even though the answers primarily confirm that people keep animals for their own survival and for financial reasons, it also includes information and formulations that bear witness to concern for the animals. In order to understand how close association with domestic animals in the past could generate such feelings, it is important to reflect over the division of work between the sexes in agriculture, together with the fact that deficiencies for people also meant deficiencies for animals, both physically and emotionally.